1996
DOI: 10.1002/(sici)1097-4644(19960915)62:4<484::aid-jcb6>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Transport of CaM kinase along processes elicited by neuronal contact evokes an inhibition of arborization and outgrowth in D. melanogaster cultured neurons

Abstract: Transgenic Drosophila strains expressing an inhibitory peptide of Ca2+/calmodulin dependent protein kinase II (CaM kinase), or a constitutively activated CaM kinase, show altered neuronal process morphology compared to wild type in scanning electron microscopy (SEM) of cultured mature neurons from embryonic neuroblasts. We observed significantly enhanced process growth in cells with inhibited enzyme, and reduced process growth in cells with activated enzyme, suggesting that active CaM kinase is involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…1993) (maximum ratio after 15 h: 5.05 ± 0.6 and 3 ± 0.35 for systems with and without denatonium, respectively, t = 2.64, P = 0.01, df = 18). On the other hand, RQED which expresses Cam kinase II under heat shock promoter (Broughton et al . 1996) showed a pattern not substantially different from C‐S (maximum ratio obtained for RQED with the denatonium system, 3.3 ± 0.15 vs. 2.7 ± 0.25 for C‐S ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1993) (maximum ratio after 15 h: 5.05 ± 0.6 and 3 ± 0.35 for systems with and without denatonium, respectively, t = 2.64, P = 0.01, df = 18). On the other hand, RQED which expresses Cam kinase II under heat shock promoter (Broughton et al . 1996) showed a pattern not substantially different from C‐S (maximum ratio obtained for RQED with the denatonium system, 3.3 ± 0.15 vs. 2.7 ± 0.25 for C‐S ).…”
Section: Resultsmentioning
confidence: 99%
“…1987; Levin et al . 1992) is an adenyl cyclase mutant with a low level of cAMP, RQED (Broughton et al . 1996) over‐expresses Cam kinase II under heat shock promoter and ala 2 (Griffith et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila melanogaster has a single CaMK-II gene, from which at least five variants are expressed that are important in development and behavior (Griffith and Greenspan, 1993;Ohsako et al, 1993;Takamatsu et al, 1994;VanBerkum and Goodman, 1995;Broughton et al, 1996;VanBerkum, 1996;Kahn and Matsumoto, 1997;Koh et al, 1999;Beumer et al, 2002). The single CaMK-II gene in the nematode Caenorhabditis elegans (unc-43) has been implicated in diverse behavioral phenomena (Reiner et al, 1999;Troemel et al, 1999;Wang and Wadsworth, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of Drosophila neurons revealed an inhibitory role of CaMKII on neurite branching (Broughton et al, 1996). In contrast, CaMKII expression in the dendritic arbors of sensory neurons increased the dynamic nature and formation of filopodia during development (Andersen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%